LANDASAN FILOSOFIS DAN TEOLOGIS PAI DALAM PENGUATAN PENDIDIKAN KARAKTER: PERSPEKTIF GURU DAN SISWA - Musdalifah; Ridwan Idris; Rappe (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study explores the philosophical and theological foundations of Islamic Religious Education (Pendidikan Agama Islam/PAI) in strengthening character education from the perspectives of teachers and students. Using a qualitative approach with interview methods involving 8 teachers and 16 students from elementary schools in Sorong, this research aims to understand how philosophical and theological values of Islam are integrated into character education practices. The results show that teachers and students view PAI as fundamental in forming good character traits aligned with Islamic values. The philosophical foundation emphasizes the holistic development of human personality, while the theological foundation roots character education in divine values. Both perspectives recognize the importance of integrating Islamic teachings with character education to create morally responsible individuals. This study contributes to understanding the implementation of character education through the lens of Islamic philosophy and theology.